PENGEMBANGAN SUBJECT SPECIFIC PEDAGOGY BERBASIS PROBLEM BASED LEARNING UNTUK PENGUATAN SIKAP PEDULI LINGKUNGAN SISWA KELAS VII SMP - Nugroho, Wahyu Adhi; Karyanto, Puguh; Nurmiyati, Nurmiyati (BIO-PEDAGOGI, 2016)
This research considered as Research and Development. The reseach conducted from January to May 2016. The purpose of this research is to develope Subject Spesific Pedagogy (SSP) based on Problem Based Learning (PBL) to reinforce student’s environmental-caring attitude in Grade VII SMP Negeri A Karanganyar academic year 2015/2016. The population of this research was of class VII in SMP N A Karanganyar. Class VII H and VII I were selested as the sample of research. The research design is 4D (four-D) by Thiagarajan. This research model consist of define, design, and develope. The disseminate phase was excluded in this research because the purpose of this research only develope product SSP based on PBL. The characteristic of product is integration of PBL syntax and enviromental subject. The result of validation from expert judgements showed that 90% in RPP (valid), 90% in module (valid), 90% in LKS (valid), and 83% in instrument of evaluation (valid). The development testing result from teacher and students showed that 84% and 79% in modul and LKS (valid). SSP based on PBL is effective to improve environmental-caring attitude. NEP data showed that the mean value of all aspect had been improved from 48,39% up to 54,86%. Paired sample’s t-test showed that sig=0,000 < α=0,05 it’s mean there was differences students environmental-caring attitude between pre and post-treatment. The conclusion of this this research showed that SSP based on PBL is valid and proper for Grade VII SMP N A Karanganyar. Keywords : Subject Spesific Pedagogy, Problem Based Learning, Environmental-Caring Attitude, New Ecological Paradigm